(untitled) (Journal of actual problems of jurisprudence, 2018)
In the article examined to the role of the special knowledge for the exposure of criminal adaptations for stage and another receptions of concealment in economic crimes. From the criminalistics point of view, the special economic knowledge it is necessary to consider the means of exposure and recognition of signs of concealment of event of crime. Adaptation of separate positions of the certain economic fields of knowledge is obligatory pre-condition of increase of efficiency of fight against economic criminality. Key words: economic crimes, special knowledge, specialist, criminal adaptation for stage, audit, revision.